The Colombian Communist Party, the FARC and the Problem of Armed Struggle in the 1980s - Manukhin Alexey (Латиноамериканский исторический альманах)
In the history of Latin American radical left movements in the second half of the twentieth century, one of the key themes is the importance of armed struggle as an instrument of revolu-tionary activity. The 1980s became an important stage in their development, when many rebel groups embarked on the path of legalization. The article examines the experience of Co-lombia, which experienced the slow formation of a pluralistic political system during this period. The object of the study is the relationship of the Colombian Communist Party (Partido Comunista Colombiano, PCC) with the rebel movements, primarily the Revolutionary Armed Forces of Colombia–the Army of the People (Fuerzas Armadas Revolucionarias de Colombia – Ejército del Pueblo, FARC–EP). It is noted that the commitment to the principle of "combining all forms of struggle" has led to the preservation of close ties with the FARC, despite the distancing of the two organizations from each other in terms of governance and goals. In the 1980s. The PCC intensified its efforts to strengthen cooperation with broad strata of the left, including with the aim of creating elec-toral associations, which ensured the emergence in 1985. The Patriotic Union (Unión Patriótica, UP). This association was intended to serve as a channel for the FARC to enter political life. The issue of the truce between the FARC and the gov-ernment, as well as the relationship to other rebel movements, has become an important subject of internal debate in the PCC ranks against the background of the large-scale terror unleashed against the UP and the problem of democratizing the Communist Party. In conclusion, it is concluded that the slow ideological evolution of the PCC has become one of the reasons for the difficulties in ending the armed conflict in Colombia.